Implementasi Program Rumah Anak Prestasi oleh Dinas Sosial Kota Surabaya - Rahmawati, Dina Ayu; Hawa, Alvi Ismatul; Novita, Noftarida Dina; Sibarani, Anggie Amalia Sukmana; Tukiman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is motivated by the fulfillment of rights for children with special needs that need to be equal to other normal children. Inclusive schools and special schools cannot fulfill them due to several factors such as expensive costs, lack of facilities and qualified teaching staff for children with disabilities. The existence of the Rumah Anak Prestasi Program by the Surabaya City Social Service is a space for children with disabilities to develop their abilities. The results showed a positive response through David Corten's program implementation theory. Program and program implementers indicators show that RAP is a program that parents of children with disabilities look forward to. Complete and free facilities, as well as teaching staff who are in accordance with their fields are devoted to serving children with disabilities in the city of Surabaya. The target group indicators show that satisfaction from parents of children with disabilities at RAP Semolowaru is a positive response that can help the RAP program develop. The conclusion of this research is that the Semolowaru RAP program has successfully implemented to reduce the anxiety of parents and children with disabilities regarding stimulus training for children with disabilities in Surabaya City This research is motivated by the fulfillment of rights for children with special needs that need to be equal to other normal children. Inclusive schools and special schools cannot fulfill them due to several factors such as expensive costs, lack of facilities and qualified teaching staff for children with disabilities. The existence of the Rumah Anak Prestasi Program by the Surabaya City Social Service is a space for children with disabilities to develop their abilities. The results showed a positive response through David Corten's program implementation theory. Program and program implementers indicators show that RAP is a program that parents of children with disabilities look forward to. Complete and free facilities, as well as teaching staff who are in accordance with their fields are devoted to serving children with disabilities in the city of Surabaya. The target group indicators show that satisfaction from parents of children with disabilities at RAP Semolowaru is a positive response that can help the RAP program develop. The conclusion of this research is that the Semolowaru RAP program has successfully implemented to reduce the anxiety of parents and children with disabilities regarding stimulus training for children with disabilities in Surabaya City